Is Peer assisted learning better? A modern question to answer: a comparative study - Khola Waheed Khan; Shezadi Sabah Imran; Musarat Ramzan; Imrana Maqsood (Journal of the Pakistan Medical Association, 2021)
Published in August 2021.